Relaxing Competition through Speculation: Committing to a Negative Supply Slope - Pär Holmberg; Bert Willems (Research Institute of Industrial Economics (IFN), 2012)
We demonstrate how suppliers can take strategic speculative positions in derivatives markets to soften competition in the spot market. In our game, suppliers first choose a portfolio of call options and then compete with supply functions. In equilibrium firms sell forward contracts and buy call options to commit to downward sloping supply functions. Although this strategy is risky, it reduces the elasticity of the residual demand of competitors, who increase their mark-ups in response. We show that this type of strategic speculation increases the level and volatility of commodity prices and decreases welfare.
Keywords: C73; D43; D44; G13; L13; L94; 330; Supply function equilibrium; Option contracts; Strategic commitment; Speculation; Derivat; Anlageverhalten; Institutioneller Investor; Spotmarkt; Unvollkommener Markt; Spieltheorie